Endocrine Disrupting Chemicals and Reproductive Health in Boys and Men - Rodprasert, Wiwat; Toppari, Jorma; Virtanen, Helena E. (Frontiers in Endocrinology, 2021)
Male reproductive health has declined as indicated by increasing rate of cryptorchidism, i.e. undescended testis, poor semen quality, low serum testosterone level and increasing rate of testicular cancer. Exposure to endocrine disrupting chemicals (EDCs) is proposed as one of possible causes that have a role on this finding. In utero exposure to antiandrogenic EDCs, particularly at a sensitive period of fetal testicular development, the so called ‘masculinization programming window (MPW)’, can disturb testicular development and function. The decreased androgen effects during the MPW can cause both short- and long-term reproductive disorders. A concurrent exposure to EDCs may also affect testicular function or damage testicular cells. Evidence from animal studies supports the role of endocrine disrupting chemicals in development of male reproductive disorders. However, evidence from epidemiological studies is relatively mixed. In this article, we review the current literature that evaluated relationship between prenatal exposure and anogenital distance and the prevalence of cryptorchidism and congenital penile abnormality called hypospadias. We analyzed also association between prenatal and postnatal EDC exposure and semen quality, hypothalamic-pituitary-gonadal axis hormone levels and testicular cancer.